2020
DOI: 10.1177/1046878120903467
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Two Different Structures for Debriefing in Simulation: The Influence of the Structure on the Facilitator Role

Abstract: Background. In the use of simulation as a learning approach, a structured debriefing is important for students to achieve learning. The facilitator's feedback style and abilities in facilitating are crucial, and have a great impact on the learning environment. The facilitators should facilitate for student active learning, and provide helpful feedback to empower students as self-regulated learners. The aim of the study was to explore the Steinwachs structure and the Critical Response Process structure when use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…Participants in our study highlighted the essential role of structured debriefing to support student learning through ISBL, and this aligns with other studies (Hall & Tori, 2017; Tosterud et al, 2020). Tosterud et al (2020) explored two different forms of structure that can be used for debriefing. The first of these is the Steinwachs structure, which includes the description phase requested by the students in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Participants in our study highlighted the essential role of structured debriefing to support student learning through ISBL, and this aligns with other studies (Hall & Tori, 2017; Tosterud et al, 2020). Tosterud et al (2020) explored two different forms of structure that can be used for debriefing. The first of these is the Steinwachs structure, which includes the description phase requested by the students in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The second is the Critical Response Process, in which the facilitator begins the debriefing by inviting respondents to highlight what particular aspects of the implementation impressed them or seemed like good practice. The Steinwachs structure seems to emphasise the facilitator's frames rather than student involvement (Tosterud et al, 2020). This does not align well with the present findings, as participants reported that the description phase is important to develop a shared understanding of what happened for further exploration of events in the simulation session.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting a formal structure to debriefing has been found to improve student learning outcomes and assist in the acquisition and development of student competencies (da Silva et al, 2020). Although multiple models of debriefing exist, many nurse educators perceive a structured approach to debriefing as essential to simulation effectiveness (Mariani et al, 2014;Tosterud et al, 2020), and we have found this to be true also in the context of study abroad. Our structured approach provides a focused discussion and not one that moves randomly from one thought or topic to another.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 73%
“…Inspired by this, we decided to conduct a study using a quasi-experimental multi-method, comparative design. A full presentation of the study has been published [19]. Two structures for debriefing were included.…”
Section: Exploring Two Structures For Debriefing and How They Influen...mentioning
confidence: 99%